2022
DOI: 10.3389/fpsyg.2022.900546
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Effect of Cultural Intelligence on the Relationship Between Emotional Intelligence and Job Satisfaction

Abstract: It is seen that employees with high emotional intelligence (EI) generally have low level of job stress; they can also integrate better with their jobs and provide a high level of job satisfaction (JS). This study aims to investigate the moderating effect of the cultural intelligence (CI) level of academicians on the relationship between their EI and JS. The data were collected from 470 academicians working in Turkish universities. The sample consists of 3 sub-groups: academicians that are Turkish citizens of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Employees with high EI generally have lower levels of job stress. They can also provide a high level of job satisfaction [29]. Both internal and external factors play a fundamental role in job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Employees with high EI generally have lower levels of job stress. They can also provide a high level of job satisfaction [29]. Both internal and external factors play a fundamental role in job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the relationship between CI and emotional well-being, Le et al (2020) found that the metacognitive dimension of CI is positively and statistically significantly related to subjective well-being. Furthermore, the job satisfaction dimension of emotional well-being has been found to be positively related to CI (Bal & Kökalan, 2022; Licki & van der Walt, 2021). The relationship established between CI and psychological well-being confirms the findings of Chen (2015) and Ayoob et al (2015) that CI influences psychological well-being, despite the differences in context and samples between those studies and the current study.…”
Section: Discussion and Practical Implicationsmentioning
confidence: 99%
“…In addition, managers deploy EQ in interpersonal interactions to foster a work climate where employees are happy and engaged (Udod et al, 2020). Given the difficulties of running a business and managing people, it should be clear how crucial it is for a leader to possess this quality (Bal & Kökalan, 2022). Influential leaders have a more significant amount of EQ to create a favorable work environment, build strong working associations, and inspire their team members (Zaman et al, 2021).…”
Section: Emotional Intelligence As Mediatormentioning
confidence: 99%